2005
DOI: 10.1577/t05-054.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Size‐Selective Mortality after the First Summer of Ocean Growth by Pink Salmon

Abstract: Pink salmon Onchorhynchus gorbuscha with identifiable thermal otolith marks from Prince William Sound hatchery release groups during 2001 were used to test the hypothesis that faster-growing fish during their first summer in the ocean had higher survival rates than slowergrowing fish. Marked juvenile pink salmon were sampled monthly in Prince William Sound and the Gulf of Alaska, and adults that survived to maturity were recovered at hatchery release sites the following year. Surviving fish exhibited significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
91
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 32 publications
9
91
0
1
Order By: Relevance
“…This study extends the analysis by Moss et al (2005) to an interannual comparison of the timing and magnitude of differences in the growth and size of juveniles versus returning adults. Our main objective was to use scale patterns to compare the growth of juvenile pink salmon collected during July-September 2001 and that of surviving adults from the same year-class.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…This study extends the analysis by Moss et al (2005) to an interannual comparison of the timing and magnitude of differences in the growth and size of juveniles versus returning adults. Our main objective was to use scale patterns to compare the growth of juvenile pink salmon collected during July-September 2001 and that of surviving adults from the same year-class.…”
mentioning
confidence: 57%
“…The first weeks at sea are thus often referred to as a ''critical period'' for growth in salmon because significant mortality occurs during this time (Parker Beamish and Mahnken 2001). Pink salmon are hypothesized to undergo a second critical period after the first growing season, presumably during the winter Mahnken 1999, 2001;Moss et al 2005). Under the ''critical size/critical period'' hypothesis, juvenile salmon that do not achieve a threshold size by the end of their first summer at sea will not survive the following winter (Beamish and Mahnken 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies of Pacific salmon Oncorhynchus spp. have shown that individuals that survive to adulthood were often larger than average as juveniles (Beamish et al 2004;Zabel and Achord 2004;Moss et al 2005;Claiborne et al 2011; Thompson and Beauchamp 2014), and growth rates during initial marine residence are often correlated with survival in both Atlantic Salmon Salmo salar and Pacific salmon (Holtby et al 1990;Jonsson et al 2003;Miller et al 2014) and marine fish in general (Sogard 1997). However, while variation in timing and size at ocean entry is well documented between species or populations occupying independent river basins (e.g., Groot and Margolis 1991;Quinn 2005;Spence and Hall 2010), far less is known about the variation among populations within basins that enter the ocean at a common location (Beamish et al 2013).…”
mentioning
confidence: 99%